500 plates & chargers : innovative expressions of function & style - Tourtillott, Suzanne J. E. (Lark ceramics book, 2008)
Plates and chargers can serve as more than just places to put your food: they can be glorious art to show off on a table, sideboard or dresser. This title features 500 pieces that range from the utilitarian yet beautifully glazed plate to dramatically decorated work and they're crafted from a variety of materials - including pristine porcelain